2021
DOI: 10.1177/1932202x211013806
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Academic Talent Development of Black Girls in K-12: A Systematic Review

Abstract: Black girls experience numerous challenges to their academic development. This study examines the literature from the last 30 years related to the influences on the academic talent development of school-aged Black girls. Environmental and intrapersonal influences to Black girls academic talent development are explored. Using a systematic approach, 43 articles are reviewed and summarized. Thematic analysis conducted on the results and findings sections from each article reveal four major themes related to perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…Articles with a score of 15 or above were included in this review. The assessment score of 15 out of 28 in our review was based on methodologies used in different peer-reviewed articles (e.g., Alangari, 2022;Davis, 2021;Margot & Kettler, 2019). Among the included articles, 10% scored between 15 and 19, 60% scored between 20 and 24, and the remaining 30% achieved scores ranging from 25 to 28.To ensure objectivity, in addition to the two research experts, the second author reviewed all 33 selected articles and confirmed that all retained articles met the quality criteria.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Articles with a score of 15 or above were included in this review. The assessment score of 15 out of 28 in our review was based on methodologies used in different peer-reviewed articles (e.g., Alangari, 2022;Davis, 2021;Margot & Kettler, 2019). Among the included articles, 10% scored between 15 and 19, 60% scored between 20 and 24, and the remaining 30% achieved scores ranging from 25 to 28.To ensure objectivity, in addition to the two research experts, the second author reviewed all 33 selected articles and confirmed that all retained articles met the quality criteria.…”
Section: Data Collection and Analysismentioning
confidence: 99%